Transferrin-based radiolabeled probe predicts the sensitivity of human renal cancer cell lines to ferroptosis inducer erastin - Shibata, Yuki (Biochem Biophys Rep, 2021)
Ferroptosis induction has been recognized as a novel cancer therapeutic strategy. To effectively apply ferroptosis-targeting cancer therapy to individual patients, a diagnostic indicator for selecting this therapeutic strategy from a number of molecular targeting drugs is needed. However, to date, methods that can predict the efficacy of ferroptosis-targeting treatment have not been established yet. In this study, we focused on the iron metabolic pathway to develop a nuclear imaging technique for diagnosing the susceptibility of cancer cells to ferroptosis. As a nuclear probe, human transferrin (Tf) was labeled with Gallium-68 ((68)Ga) using 2-(p-isothiocyanatobenzyl)-1,4,7-triazacyclononane-1,4,7-triacetic acid (NOTA) as a chelator ((68)Ga-NOTA-Tf). Western blot assay and clonogenic survival assay with human renal cancer cell lines A498 and 786-O revealed that the protein expression level of transferrin receptor1 (TfR1) and sensitivity to a ferroptosis inducer, erastin, were correlated. A cellular uptake assay with (68)Ga-NOTA-Tf revealed that the cancer cells sensitive to erastin highly internalized the (68)Ga-NOTA-Tf. Furthermore, treatment with the TfR1 inhibitor ferristatin II reduced the cellular uptake of (68)Ga-NOTA-Tf, indicating that the intracellular uptake of the probe was mediated by TfR1. These results suggest that (68)Ga-NOTA-Tf can be useful in predicting the sensitivity of cancer cells to ferroptosis inducers.